The Influence of Islamic Financial Planning in Buying Life Insurance - Ardhina, Aried; Ali, Zulkarnain Muhammad; Indra, Indra (PT Inovasi Pratama Internasional, 2024)
In Indonesia there is still a big opportunity to develop the sharia industry in Indonesia, especially sharia life insurance. This is based on the penetration rate of life insurance in Indonesia in 2018 only reaching 1.3%, which shows a decrease from the previous year which was 1.4%. Therefore a strategy is needed to increase the penetration of sharia insurance through research on the factors that influence a person's interest in participating in sharia life insurance. This study aims to examine the effect of financial literacy, Islamic life insurance knowledge, Islamic financial planning, and financial behavior on interest in participating in Islamic life insurance. This research is a quantitative research. Primary data was obtained through a survey that obtained 140 respondents aged over 17 years and domiciled in the city of Bogor. The analysis uses the Partial Least Square Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The results of this study indicate that the variable knowledge of sharia life insurance and sharia financial planning has a significant effect on interest in participating in sharia life insurance. On the other hand, the variables of financial literacy and financial behavior do not significantly influence interest in participating in sharia life insurance.